A history of data visualization and graphic communication - Friendly, Michael; Wainer, Howard (Harvard University Press, 2021)
"Statistical graphing was born in the seventeenth century as a scientific tool, but it quickly escaped all disciplinary bounds. Today graphics are ubiquitous in daily life. Michael Friendly and Howard Wainer detail the history of data visualization and argue that it has not only helped us solve problems, but it has also changed the way we think"--